THE INFLUENCE OF LEARNING INTERESTS, FAMILY ENVIRONMENT AND SCHOOL ENVIRONMENT ON ACCOUNTING PRACTICUM LEARNING OUTCOMES - Handayani, Nur Ayu; Mardi; Sumiati, Ati (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2021)
This study aims to determine the effect of interest in learning, family environment, and school environment on the improvement of learning outcomes of Accounting Practicum for the Service and Trade Company in grades XI and XII students majoring in Accounting at SMK Negeri 3 Jakarta. This research uses a quantitative approach with a survey method. The study population was 105 students. The sample used was 84 students using the Simple Random Sampling technique. The results of the study found that there was a significant and positive effect simultaneously between interest in learning, the family environment and the school environment on improving learning outcomes. Furthermore, the test results concluded that interest in learning has a positive effect on learning outcomes. The family environment has a positive effect on learning outcomes. Then the school environment has a positive effect on learning outcomes.